The Analysis of Ecological Awareness of Students of SMK Migas Cepu - Fitriah Hanim; Djono Djono; Susanto Susanto (BIRCU, 2021)
The history of petroleum in Cepu, which has not been explored and taught to students, makes students' knowledge of the environment low. This study aims to analyze the extent to which students' knowledge of the environment and ecological awareness possessed by students of SMK Migas Cepu. By using the case study method, the principles of ecological literacy outlined by the researcher in the form of a questionnaire become the basis for knowing students' understanding and awareness of their environment. To provide students with an understanding of the negative impact of oil refineries in relation to fostering attitudes and knowledge of ecology, researchers provide learning the history of petroleum through the guided inquiry method with the aim of helping students to bring up character values, namely a caring attitude towards the environment. The resultthat the significance of 0.000 <0.05, it can be concluded that H0 is rejected and H1 is accepted that There is a mean difference between the control and experimental classes. So that dapat disimreport that the questionnaire developed was effective in increasing students' ecological awareness.